Distribution and phylogeny of anaerobic ammonium-oxidizing (anammox) bacteria in the water column of the central Pacific Ocean. (October 2018) - Hamasaki, Koji; Shishikura, Ryuki; Suzuki, Shotaro; Shiozaki, Takuhei; Ogawa, Hiroshi; Nakamura, Tomotaka; Suwa, Yuichi
Abstract: Anaerobic ammonium-oxidizing (anammox) bacteria produce dinitrogen gas from nitrite and ammonium under anoxic conditions and significantly contribute nitrogen removal processes in marine environments. Distribution and activity of anammox bacteria in a marine water column have been well studied in some oxygen deficient waters such as Black Sea, Arabian Sea, Namibian upwelling and Peruvian upwelling systems. However, the habitable area of anammox bacteria in the Pacific Ocean is still an open question. Here, we report distribution, abundance and phylogeny of anammox bacteria in the water column along the north-south transect (40⁰S to 55⁰N, 170⁰W) of the Pacific Ocean in order to determine their habitable area in the open ocean. Anammox bacteria-specific 16S rRNA gene was detected at 10 locations mostly from oxygen minimum depths (OMD) where dissolved oxygen (DO) concentration ranged from 10.9 to 46.2 µmol Kg -1 . Their abundance measured by qPCR ranged from 3.69 ± 1.35 × 10 2 copies L -1 to 474 ± 15 × 10 2 copies L -1 . The phylogenetic analysis showed that anammox bacteria detected in this study were all related to Candidatus Scalindua species and clustered into three subgroups: the Scalindua brodae/sorokinii cluster, the sediment cluster and the Arabian Sea cluster. Relationship between the abundance of anammox bacteria and DO concentration varied among these 3 clusters, suggesting their difference in oxygen sensitivity. Although rate measurement of anammox reaction using 15 N-labeled substrates failed for all OMD samples tested during the cruise, this study unveiled the distribution of anammox bacteria in the open ocean oxygen minimum zone (OMZ) where oxygen deficiency is not extreme but moderate, which provides an insight into the potential distribution of anammox bacteria in marine environments.